Water quality assessment of river based on phytoplankton biological integrity index in rural areas of the upstream Citarum River, West Java, Indonesia - DESTY PRATIWI; DINA OKTAVIA; DADAN SUMIARSA; SUNARDI SUNARDI (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Pratiwi D, Oktavia D, Sumiarsa D, Sunardi S. 2024. Water quality assessment of river based on phytoplankton biological integrity index in rural areas of the upstream Citarum River, West Java, Indonesia. Biodiversitas 25: 881-889. The deterioration of water quality in the upstream Citarum River is one of the consequences of agricultural practices characterized by fertilizer and pesticide runoff that disrupts the ecological balance of aquatic ecosystems. The research area was on agricultural land use in the Cihawuk segment, Kertasari, Bandung District. The present study attempts to community structure and assess the water quality using the biological indexes of rural areas in upstream Citarum River through phytoplankton studies. A purposive sampling technique was used to collect data on physico-chemical parameters and phytoplankton community structure from stations selected on the basis of agricultural land use. Furthermore, biological indexes such as pollution levels based on the Shannon Wienner diversity index (H'), Palmer algae index, and Diatomeae index are examined using the data community structure of phytoplankton. The findings show that the abundance of phytoplankton in rural areas is 4,105 cells/L. The community structure of phytoplankton was dominated by Coelastrum sp. and Trachellomonas sp. The Palmer algae index ranges from 23-26, indicating that the water was a highly organic pollutant. The pollution level of upstream Citarum River based on the diversity index shows moderately polluted water. Meanwhile, the diatomeae index showed less than 0.2, which sites water bodies were mesotrophic. Phytoplankton and their indexes serve as valuable tools for evaluating the quality of the water environment.